A Single Protein Kinase A or Calmodulin Kinase II Site Does Not Control the Cardiac Pacemaker Ca2+ Clock. (February 2016) - Wu, Yuejin; Valdivia, Héctor H.; Wehrens, Xander H.T.; Anderson, Mark E.
Abstract : Background—: Fight or flight heart rate (HR) increases depend on protein kinase A (PKA)– and calmodulin kinase II (CaMKII)–mediated enhancement of Ca 2+ uptake and release from sarcoplasmic reticulum (SR) in sinoatrial nodal cells (SANC). However, the impact of specific PKA and CaMKII phosphorylation sites on HR is unknown. Methods and Results—: We systematically evaluated validated PKA and CaMKII target sites on phospholamban and the ryanodine receptor using genetically modified mice. We found that knockin alanine replacement of ryanodine receptor PKA (S2808) or CaMKII (S2814) target sites failed to affect HR responses to isoproterenol or spontaneous activity in vivo or in SANC. Similarly, selective mutation of phospholamban amino acids critical for enhancing SR Ca 2+ uptake by PKA (S16) or CaMKII (T17) to alanines did not affect HR in vivo or in SANC. In contrast, CaMKII inhibition by expression of AC3-I has been shown to slow SANC rate responses to isoproterenol and decrease SR Ca 2+ content. Phospholamban deficiency rescued SR Ca 2+ content and SANC rate responses to isoproterenol in mice with AC3-I expression, suggesting that CaMKII affects HR by modulation of SR Ca 2+ content. Consistent with this, mice expressing a superinhibitory phospholamban mutant had low SR Ca 2+ content and slow HR in vivo and in SANC. Conclusions—: SR Ca 2+ depletion reduces HR and SR Ca 2+ repletion restores physiological SANC rate responses, despite CaMKII inhibition. PKA and CaMKII do not affect HR by a unique target site governing SR Ca 2+ uptake or release. HR acceleration may require an SR Ca 2+ content threshold. Abstract : Supplemental Digital Content is available in the text.